The Chronobiological and Neuroprotective Mechanisms of Resveratrol in Improving Sleep - Wenwen Zhu; Ailin Gong; Bin Zhang; Hanxing Cheng; Lishan Huang; Xiao Wu; Dechou Zhang; Wenbin Dai; Sen Li; Houping Xu (Mediators of Inflammation)
According to statistics, more than one-third of the global population currently experiences sleep problems, and about 10% of adults have been diagnosed with insomnia, a proportion that is increasing annually. Most currently used insomnia medications are not specifically developed but are discovered by chance, often resulting in unavoidable side effects like addiction. Thus, there is an urgent need to find safer and more effective therapeutic options. Resveratrol, a natural polyphenolic compound, shows significant potential in improving insomnia. Research shows that its effects may be achieved through multiple biological processes, including antiapoptosis, antioxidant activity, anti-inflammation, circadian rhythm regulation, modulation of neurotransmitters (gamma-aminobutyric acid (GABA), DA, 5-HT, cortisol), and increased levels of neurotrophic factor BDNF. Additionally, resveratrol’s treatment of insomnia is closely linked to the SIRT1, AMPK, NF-κB, mTOR, PI3K/Akt, and MAPK pathways. This review summarizes the mechanisms of resveratrol in treating insomnia to provide researchers with a deeper understanding of its action, which can aid in the development of novel targeted drugs and offer innovative ideas and methods for clinical insomnia treatment.